2018
DOI: 10.1007/s11150-018-9438-9
|View full text |Cite
|
Sign up to set email alerts
|

How does family health care use respond to economic shocks? realized and anticipated effects

Abstract: Families in constrained economic circumstances resulting from economic shocks face difficult choices regarding how best to spend their diminished resources. As families strive to preserve their living standards, decisions regarding health care use and its allocation among family members may become more discretionary and complex. Using two-year panel data from the Medical Expenditure Panel Survey for 2004 to 2011, we examine how the intra-family allocation of health care spending responds to realized and antici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Lifestyle variables consisted of physical activity (less than once a week, 1-3 times a week, more than three times per week) and smoking status (non-smoker, occasional smoker, regular smoker). Health shocks (illness) or financial distress can influence the choice of healthcare utilisation [32,33]. Therefore, health shocks and financial distress were measured thus: serious personal illness (yes =1, no = 0) and major worsening in finances (yes =1, no = 0), either of these in the last twelve months.…”
Section: Variable Selections and Measuresmentioning
confidence: 99%
“…Lifestyle variables consisted of physical activity (less than once a week, 1-3 times a week, more than three times per week) and smoking status (non-smoker, occasional smoker, regular smoker). Health shocks (illness) or financial distress can influence the choice of healthcare utilisation [32,33]. Therefore, health shocks and financial distress were measured thus: serious personal illness (yes =1, no = 0) and major worsening in finances (yes =1, no = 0), either of these in the last twelve months.…”
Section: Variable Selections and Measuresmentioning
confidence: 99%
“…Finally, we further examine whether the change in its out-of-pocket health care spending burden is differentially borne by single-mother families compared to two-parent families. In earlier work examining the impact of economic shocks on the intra-family allocation of health care spending between adults and children (Monheit, Grafova, and Kumar 2018), we found that the response was largely due to the behavior of single-mother families.…”
Section: Introductionmentioning
confidence: 73%
“…2 For consistency with our earlier analyses of economic shocks and family health security (Monheit, Grafova, and Kumar, 2018;Grafova, Monheit and Kumar 2018;and Monheit and Grafova, 2018), we rely on data for this period.…”
Section: Datamentioning
confidence: 99%
“…2 Since the focus of our analysis is on the family's health care spending burden, we constructed family units and obtained family-level characteristics for each year of our two-year panels based on the characteristics of individual family members, family-level income, the insurance status of each family member, and each parent's employment history. Our sample of families consists of those with all members present for both years of the two-year panel and who 2 For consistency with our earlier analyses of economic shocks and family health security (Monheit, Grafova, and Kumar, 2018;Grafova, Monheit and Kumar 2018;and Monheit and Grafova, 2018), we rely on data for this period.…”
Section: Datamentioning
confidence: 99%